Comparative evaluation of two automated ID/AST systems and mikrolatest kit in assessing the In Vitro colistin susceptibility of carbapenem-resistant enterobacteriaceae isolates: A single-center exploratory study from North India - Mohit Bhatia; Ravi Indrapal Singh; Diksha Rani; U Sasi Rekha; Ranjana Rohilla; Balram Ji Omar; Pratima Gupta (Wolters Kluwer Medknow Publications, 2022)
Aims: To generate preliminary data about comparative evaluation of two automated ID/AST systems and Mikrolatest kit in determining in vitro colistin susceptibility of carbapenem-resistant Enterobacteriaceae spp. Materials and methods: Twenty-three carbapenem-resistant Escherichia coli and Klebsiella pneumoniae and two carbapenem-sensitive multidrug-resistant E. coli isolates obtained from various clinical samples of inpatients were included in the study. Species-level identification and antibiotic susceptibility testing (AST) of test isolates was performed using BD phoenix and MicroScan WalkAway 96 Plus automated systems. Identity was reconfirmed by matrix-assisted laser desorption ionization-time-of-flight mass spectrometry (MALDI-TOF MS). Additional colistin susceptibility testing was performed using Mikrolatest MIC colistin susceptibility testing kit (reference method). Results: Results showed that 16% isolates (27.3% [3/11] K. pneumoniae and 7.1% [1/14] E. coli) exhibited in vitro colistin resistance by the reference method. While the categorical agreement between BD Phoenix M50 ID/AST system and reference test w. r. t in vitro colistin susceptibility results was 100% and 92.9% for K. pneumoniae & E. coli, respectively, it was much lower between MicroScan WalkAway 96 plus ID/AST system and the latter. Almost perfect agreement (96%; kappa: 0.834) was observed between BD Phoenix M50 system and reference method. Conclusions: The results of this study are preliminary and cannot be generalized. Multicentric studies with large sample sizes should be conducted throughout the country to gain a deeper understanding of the subject under consideration.